2017
DOI: 10.1021/acsami.6b15995
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidizing Gas Sensing and Dominant Sensing Mechanism of n-CaO-Decorated n-ZnO Nanorod Sensors

Abstract: In this work, we investigated the NO and CO sensing properties of n-CaO-decorated n-ZnO nanorods and the dominant sensing mechanism in n-n heterostructured one-dimensional (1D) nanostructured multinetworked chemiresistive gas sensors utilizing the nanorods. The CaO-decorated n-ZnO nanorods showed stronger response to NO than most other ZnO-based nanostructures, including the pristine ZnO nanorods. Many researchers have attributed the enhanced sensing performance of heterostructured sensors to the modulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…The Pd-decorated ZnO nanorods showed a stable performance as well as good stability and repeatability. The response time was approximately 12 min, but the recovery time was much longer, approximately 10 h. Moreover, the CaO-decorated n-ZnO nanorods showed stronger response to NO 2 than the pristine ZnO nanorods [34].…”
Section: Decorationmentioning
confidence: 99%
“…The Pd-decorated ZnO nanorods showed a stable performance as well as good stability and repeatability. The response time was approximately 12 min, but the recovery time was much longer, approximately 10 h. Moreover, the CaO-decorated n-ZnO nanorods showed stronger response to NO 2 than the pristine ZnO nanorods [34].…”
Section: Decorationmentioning
confidence: 99%
“…While, in biosensors, different analytes can be targeted with a special biomolecule, it is an especially difficult task to differentiate among the same type of gases (oxidizing or reducing), since depletion layer width change and consequently response will be in the same direction. Selective recognition of the gases can be addressed by variations in chemical adsorption and dissociation of the target gases at the NW surface; therefore, NW sensor selectivity can be approached by several methods: NW geometry control [ 36 , 37 ], NW functionalization [ 38 , 39 ], selective contact formation [ 40 ], heterojunction [ 41 ], operating temperature modulation [ 42 ], and sensor array formation [ 43 ].…”
Section: Zno Nanowire Sensorsmentioning
confidence: 99%
“…The judicious choice of two appropriate n‐type materials to form such heterojunctions is important to optimize sensor performance and hence, this aspect has been intensely researched by many groups. Recently, we reported that in the case of a nanosensor with n–n heterostructure, if the workfunction of the decorating material was lower than that of the decorated material, the sensor showed higher response to oxidizing gases as compared to reducing gases; for example, the response of a CaO‐decorated ZnO NR sensor to NO 2 was stronger than its response to CO . We also predicted that conversely, if the workfunction of the decorating material is higher than that of the decorated material, the sensor should show higher response to reducing gases.…”
Section: Introductionmentioning
confidence: 96%
“…However, despite various advantages such as simple fabrication methods, low cost and high compatibility with other processes, the room temperature performance of semiconducting metal‐oxide (SMO)‐based sensors is currently far from satisfactory . To further improve the performance of such sensors, several techniques including doping with a noble metal or forming heterostructures have been developed. Because of their better response to analyte gases and stability in low oxygen environments, n‐type SMOs are generally much more widely used as base materials for gas sensors as compared to p‐type SMOs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation